Interventional Approach on Lung Abscess - Audina, Dea Putri; Agustin, Heidy; Reisa, Tina (Jurnal Respirologi Indonesia, 2024)
Lung abscess is a necrotic liquefaction process containing necrotic debris or fluid from the lung parenchyma tissue, creating a cavity of more than 2 cm caused by bacterial infection. The most common etiology of lung abscess is oral aspiration. With a high incidence of tuberculosis in Indonesia, Mycobacterium tuberculosis may also cause cold abscesses, although rarely reported. Several things can increase the risk of developing a lung abscess, such as oral aspiration, sepsis, and history of previous lung infection. The treatment for lung abscess was classified into two groups, the pharmacology group which uses antibiotics including clindamycin, ampicillin-sulbactam, moxifloxacin, carbapenem, and piperacillin-tazobactam; and the other group is non-pharmacology therapy including drainage which is indicated for patient with a size cavity of more than 6 cm. There are several options for drainage such as percutaneous or endoscopic drainage. Bronchoscopy may serve as a diagnostic and also intervention tool in lung abscess.